2001
DOI: 10.4049/jimmunol.167.4.2121
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Control of the Frequency and Allelic Exclusion of the Vβ Gene Rearrangement at the TCRβ Locus

Abstract: Ag receptor gene loci contain many V gene segments, each of which is recombined and expressed at a different frequency and is subject to allelic exclusion. To probe the parameters that mediate the different levels of regulation of V gene rearrangement, a Vβ gene segment together with 3.6-kb 5′ and 0.7-kb 3′ flanking sequences was inserted 6.8 kb upstream of the Dβ1 gene segment in the murine TCRβ locus. Despite its proximity to the Dβ gene segments and the Eβ enhancer, the inserted Vβ segment underwent VDJ rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…Notably, targeting of a V gene into the V-D intergenic region of the Tcr␤ locus, 7 kb upstream of D ␤ J ␤ , failed to increase its recombination frequency (62), whereas removal of the entire V-D region did (63). In the former study, it was concluded that the flanking sequences controlled V recombination frequency, independent of its location.…”
Section: Discussionmentioning
confidence: 89%
“…Notably, targeting of a V gene into the V-D intergenic region of the Tcr␤ locus, 7 kb upstream of D ␤ J ␤ , failed to increase its recombination frequency (62), whereas removal of the entire V-D region did (63). In the former study, it was concluded that the flanking sequences controlled V recombination frequency, independent of its location.…”
Section: Discussionmentioning
confidence: 89%
“…However, very limited studies have addressed the effects of such a large intron on recombination and accesibility of the TCR␤ locus. Recently, Sieh et al (17) showed that a certain V␤ gene is not strikingly altered in its recombination frequency when it was inserted 6.8 kb upstream of the D␤1-J␤1 cluster, which was estimated to be outside of the E␤ regulatory region. Using recombination activating gene (RAG)2 Ϫ/Ϫ mice, Chen et al (18) showed that expression of the V␤ germline transcription before rearrangement does not correlate with proximity to E␤ enhancer.…”
Section: Uring Early Development Of ␣␤ T Cells the Tcr␤ Gene Is Rementioning
confidence: 99%
“…While the putative global regulator might have contributed to the residual V␤13 accessibility and rearrangement observed in P13 Ϫ/Ϫ mice, our results strongly suggest that the individual promoter also plays a critical role in targeting specific V␤ gene for rearrangement. Previously, our investigators have shown that when the V␤13 gene segment together with the promoter were inserted upstream of the D␤1 gene segment, the inserted V␤13 gene segment rearranged at the same frequency as the natural copy (29). Together, these findings strongly suggest that the variable gene promoter plays an essential role in regulating local access of gene segments for rearrangement.…”
Section: Discussionmentioning
confidence: 54%
“…However, cis elements that mediate allelic exclusion are not known. When the V␤13 gene segment together with the promoter were inserted upstream of the D␤1 gene segment, the inserted V␤13 gene segment continued to rearrange in the presence of a TCR transgene expression (29), indicating that the promoter alone is not sufficient to mediate allelic exclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation